Facilitating Leadership Coach Capacity for School Leadership Development: The Intersection of Structured Community and Experiential Learning. (February 2021) - Huggins, Kristin Shawn; Klar, Hans W.; Andreoli, Parker M.
Purpose: The purpose of this article is to examine how the leadership coaching capacities of experienced school leaders can be developed to support less-experienced school leaders to lead continuous improvement efforts. In this article, we report the findings of a 2-year study of experienced school leaders who developed their leadership coaching knowledge, skills, and dispositions to enhance the capacities of less-experienced school leaders in a research–practice partnership called the Leadership Learning Community.Research Methods: We drew on qualitative research methodology to answer the study's research question. To collect our data, we utilized participant observations of 12 professional development days and 70 job-embedded coaching sessions over a 2-year period, yearly semistructured interviews with the eight leadership coach participants, and other artifacts related to the Leadership Learning Community. We analyzed our data using multiple rounds of coding to arrive at the themes.Findings: The findings highlight the possibilities of developing leadership coaching capacity through a combination of community-based structured and facilitated learning opportunities and experiential learning. The findings also add to the limited research regarding leadership coaching as a strategy for enhancing school leadership development.Conclusion and Implications: The results of the study provide assistance to national and state administrator organizations, educational service districts, and school district administrators endeavoring to meet the learning needs of school leaders through leadership coaching. Further research should be conducted to understand how the leadership coaching capacities of leadership supervisors and developers can be facilitated.